CHSY1 is upregulated and acts as tumor promotor in gastric cancer through regulating cell proliferation, apoptosis, and migration. Issue 18 (17th September 2021) - Liu, Jingjing; Tian, Zhenwei; Liu, Tianzhou; Wen, Dacheng; Ma, Zhiming; Liu, Yuanda; Zhu, Jiaming
ABSTRACT: Gastric cancer is one of the most frequently diagnosed malignant tumors, with rapid progression and poor prognosis. The role of chondroitin sulfate synthase 1 (CHSY1) in the development and progression of gastric cancer was explored and clarified in this study. The immunohistochemistry analysis of clinical tissue samples as well as data mining of public database showed that CHSY1 was significantly upregulated in gastric cancer and associated with more advanced tumor stage and poorer prognosis. In vitro loss-of-function experiments demonstrated the inhibited cell proliferation, colony formation, cell migration, as well as the promoted cell apoptosis by CHSY1 knockdown. Moreover, recovery of CHSY1 expression could attenuate the regulatory effects induced by CHSY1 knockdown. Correspondingly, gastric cancer cells with CHSY1 knockdown showed reduced tumorigenicity and slower tumor growth in vivo . In conclusion, this study identified CHSY1 as a tumor promotor in gastric cancer, which may be utilized as a novel indicator of patients' prognosis and therapeutic target for developing more effective drug for GC treatment.